Mothers’ Rights are Human Rights: Reflections on Activism and History - Ladd-Taylor, Molly (Journal of the Motherhood Initiative for Research and Community Involvement, 2014)
In popular discourse today, mothers are often set in opposition to political and evenhuman rights. Conservatives see women’s “right to choose” as an assault on the fetus’s human rights. Feminists, recalling the equality vs. difference debate, stress the incompatibilityof organizing for mothers’ rights and advancing women’s rights more broadly. Advocates of “mothers’ rights,” at least in the U.S. and Canada, usually focuson issues—such as breastfeeding, child custody, and worklife balance—associated more with the quality of life for the middle class than with conventional human rights.This article argues for a new political discourse calling for mothers’ human rights. It first reflects on two pivotal moments when the debate over mothers’ rights and entitlements entered the mainstream: the call for motherhood endowment around 1920, and the demand for welfare rights fifty years later. Since the failure of those movements, the circumstances facing U.S. mothers today has become so dire that we cannot afford not to talk about mothers’ human rights.